2020
DOI: 10.1186/s13287-020-01724-5
|View full text |Cite
|
Sign up to set email alerts
|

Adipose mesenchymal stem cell transplantation alleviates spinal cord injury-induced neuroinflammation partly by suppressing the Jagged1/Notch pathway

Abstract: Background: The therapeutic effects of adipose-derived mesenchymal stem cell (ADSC) transplantation have been demonstrated in several models of central nervous system (CNS) injury and are thought to involve the modulation of the inflammatory response. However, the exact underlying molecular mechanism is poorly understood. Activation of the Jagged1/Notch signaling pathway is thought to involve inflammatory and gliotic events in the CNS. Here, we elucidated the effect of ADSC transplantation on the inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 62 publications
1
39
0
Order By: Relevance
“…Later, we demonstrated the strong ability of mouse ADSCs to promote the expression of IL-10 and arginase 1 in macrophages and their potential to inhibit obesity-induced WAT inflammation, further confirming the regulation of ADSCs on macrophages as well as inflammatory diseases (47). In a similar manner, ADSCs induced the alternative activation of macrophages and ameliorated colitis or neuroinflammation in animal models through several different pathways or inhibitory molecules like TSG-6 (43,46,(112)(113)(114). Consistent with the roles of mouse ADSCs in obesity-induced WAT inflammation, human or rat ADSCs also displayed beneficial effects on relieving obesity-induced metabolic disorders, type 2 diabetes mellitus related complications in lung, liver, kidney, as well as cardiovascular diseases such as cardiac hypertrophy and aortic inflammation.…”
Section: Adipose Evs In Adsc-macrophage Interactionsupporting
confidence: 60%
See 1 more Smart Citation
“…Later, we demonstrated the strong ability of mouse ADSCs to promote the expression of IL-10 and arginase 1 in macrophages and their potential to inhibit obesity-induced WAT inflammation, further confirming the regulation of ADSCs on macrophages as well as inflammatory diseases (47). In a similar manner, ADSCs induced the alternative activation of macrophages and ameliorated colitis or neuroinflammation in animal models through several different pathways or inhibitory molecules like TSG-6 (43,46,(112)(113)(114). Consistent with the roles of mouse ADSCs in obesity-induced WAT inflammation, human or rat ADSCs also displayed beneficial effects on relieving obesity-induced metabolic disorders, type 2 diabetes mellitus related complications in lung, liver, kidney, as well as cardiovascular diseases such as cardiac hypertrophy and aortic inflammation.…”
Section: Adipose Evs In Adsc-macrophage Interactionsupporting
confidence: 60%
“…Accumulating data have shown that either human or mouse ADSCs have an ability to promote the alternative activation of macrophages and inhibit the inflammation of monocytes/macrophages. These effects elicited by ADSCs provided protection against several inflammatory diseases in animal models such as experimental colitis, sepsis, hepatitis and neuroinflammation (43)(44)(45)(46)(112)(113)(114). The early evidence for the regulation of ADSCs on monocytes or macrophages came from Gonzalez-Rey's study, in which human ADSCs inhibited the production of TNF-a and IL-12 from activated macrophages of septic mice.…”
Section: Adipose Evs In Adsc-macrophage Interactionmentioning
confidence: 99%
“…Currently, treatments that can promote axonal regeneration and suppress astrocytic scarring and neuroinflammation are attracting the attention of researchers [ 58 ]. Stem cell therapy has shown considerable potential for SCI treatment in recent decades [ 59 61 ]. However, several studies have found that transplantation of MSCs provides few positive efficacies on SCI due to the blood-brain barrier and immunological rejection [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Microglia maintain homeostasis of immune microenvironment of the central nervous system (CNS) 10 , 11 and play critical roles in many neurological diseases involving neuroinflammation, including stroke 12 , traumatic brain injury 13 , Parkinson’s disease 14 and spinal cord injury 15 . By suppressing microglia activation and secreting various factors including miRNAs 16 , cytokines 17 , chemokines 18 , as well as growth factors 19 , MSC-based therapies have been proposed to develop therapies for a number of neurological disorders 20 22 . However, the aforementioned MSC variations would potentially affect clinical trial outcomes.…”
Section: Introductionmentioning
confidence: 99%